KOMPETENSI GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBELAJARAN DI ERA DIGITAL - Iwantoro Iwantoro (Sekolah Tinggi Ilmu Tarbiyah (STIT) Muhammadiyah Bangil in collaboration with Association of Muslim Community in ASEAN (AMCA), 2017)
In this digital era the learning process undergoes significant changes, from teacher's approach to students to the use of media in learning. Islamic Education Teachers need to improve their competence because of the stigma that teachers of Islamic Education are said to be